FORMULAIC LANGUAGE: FIXED AND VARIED - Schmitt, Norbert (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Formulaic language has been shown to be an important component of language usage. This paper summarizes evidence of this importance and then goes on to focus upon two key characteristics of formulaic language: fixedness and variability. Formulaic language is usually conceptualized as being basically fixed, but examples are given to illustrate that in many cases formulaic language contains a considerable amount of variation. The degree and type of variation depends on which kind of formulaic language is being addressed: idiom, variable expression, or lexical bundle. Idioms, which are supposedly fixed, show the greatest amount of variation, while variable expressions and lexical bundles seem to contain much more stable fixed cores. It is suggested that variable expressions (and perhaps lexical bundles) may be stored in the mind as individual units, because there are relatively few instances to store. Conversely, idioms may involve so many variants that only the canonical form may be stored as a template, from which truncated and novel forms can be recognized. Teaching implications of these different forms of storage are considered.